The Evolving Citizen : American Youth and the Changing Norms of Democratic Engagement - Childers, Jay P., 1974- (Book collections on Project MUSE., 2012)
"Examines, through an analysis of seven high school newspapers, the evolution of civic and political participation among young people in the United States since 1965"--Provided by publisher